USABILITY EVALUATION MODEL USING CONFIRMATORY FACTOR ANALYSIS ON ONLINE BUYING SITES - Solechan, Achmad; Putra, Toni Wijanarko Adi (Jurusan Teknologi Informasi Universitas Semarang, 2022)
The data obtained from the Top brand index shows that there are 3 market leaders of online buying and selling sites in Indonesia, namely lazada.co.id; shopee.co.id and tokopedia.com. This makes the reason for choosing the object of research with the aim of research to find out the usability evaluation model using confirmatory factor analysis. The research data were obtained by distributing questionnaires as many as 150 respondents to 3 market leader online trading sites in Indonesia, namely lazada.co.id; shopee.co.id and tokopedia.com. The five components that will be used to turn into a questionnaire are learning ability, memory, efficiency, errors, satisfaction. The results showed that the design of the model in solving this particular problem is needed to measure the level of suitability of the use of the technology being made, so that research that has been carried out using the CFA method for the usability evaluation model can be concluded that by using 5 latent variables and 22 constituent indicators, resulting latent variables which are very influential in evaluating usability on online buying and selling sites. The results of the data analysis on questionnaire filling conducted by respondents were based on five variables, namely learnability, memorability, efficiency, errors and satisfaction, namely the most important factors in usability evaluation were memorability, efficiency, errors, with each index value of 5.60 in the very high category. Meanwhile, the Learnability factor has the lowest score of 5.56.